Sex Determination using Antegonial and Gonial Angle in Panoramic Radiographs: A Study on the Indonesian Population - Jauza, Nadifa Zakin; Kusuma, Ira Anggar; Keshena, Jatu Rachel (Acta Odontologica Indonesia, 2025)
Sex determination is a crucial aspect of forensic identification. This study investigates the capability of Sex determination is a crucial aspect of forensic identification. This study investigates the potential of antegonial (AGA) and gonial (GA) angle measurements on panoramic radiographs (PANs) for sex determination in an Indonesian population using logistic regression. A cross-sectional study was conducted on 300 PANs from individuals aged over 20 years, with measurements performed by two observers. Statistical analysis included independent sample t-test and logistic regression, with performance evaluated based on accuracy values. The t-test revealed significant differences in both AGA and GA between sexes. However, logistic regression yielded accuracy rates of 58% for AGA and 60.3% for GA, indicating that these variables alone are insufficient for reliable sex determination in the Indonesian population using PANs. Future studies should explore the inclusion of additional anthropometric variables from PANs to enhance the accuracy of mandibular-based sex determination methods.